The Influence of Role Playing and Simulation Learning on Critical Thinking Ability and Student Character Building - Nurhayati Nurhayati; Bahtiar Bahtiar; Hamka Hamka (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine how learning to play roles and simulations affects critical thinking skills and student character building. This study is quantitative and of the quasi-experimental variety. 38 MTsN 1 Palu City ninth graders were employed in this study. Data were gathered for this study using observation sheets for students' character development during the learning process and exams in the form of descriptions of critical thinking abilities. Descriptive and inferential statistics are used in the data analysis for this study. The study's findings demonstrate a considerable impact of simulation and role-playing learning models on students' critical thinking abilities. Students in the experimental class who were instructed using simulation and role-playing learning models scored, on average, better than those in the control class. The ability of students to formulate the main issues is the best sign of critical thinking abilities. The study's findings also demonstrate a considerable impact of simulation and role-playing learning techniques on student character development. Students in the experimental class who were instructed using role-playing learning simulations and models had an average value of character-building observations greater than those in the control class. Religious and creative activities are the best predictors of character development.